Stained glass from Welsh churches - Crampin, Martin (Y Lolfa, 2014)
This fully illustrated book brings together over six years of research and an archive of thousands of high-quality photographs, to produce a detailed narrative outlining the range and development of stained glass in Wales from the 14th century up to the present day